Parametric study of control of frequency banded behaviour of periodic pressurised composite structures - Ampatzidis, Theofanis; Chronopoulos, Dimitrios (2017)
Periodic structures are very common in engineering, such as airplane fuselages and train rails. This periodicity has been observed to be the cause of banded frequency response after mechanical excitation. This response can be engineered so that noise and vibrations to be isolated or even annihilated. In addition to this, further methods of inducing band-gaps without weight penalty are of interest among the researchers. In this paper a parametric survey was conducted examining the impact of the core geometry and the pressure in the core cells on the suppression of the vibrations. An infinite composite sandwich beam with hollow and pressurised core cells as periodic band gap inducing factors was examined. The periodic theory was used to predict the effect of pressured core cells periodicity on wave propagation and band gaps generation. Three low order finite elements (FE) models were used in this survey, which consisted of a small section of the simple sandwich beam with homogeneous core, with hollow core and with pressurised hollow core